Who does (not) benefit from entrepreneurship programs? - Lyons, Elizabeth; Zhang, Laurina (Strategic Management Journal, 2018)
[Research summary: We evaluate a technology entrepreneurship training program by comparing career decisions among applicants accepted into the program with unaccepted applicants who are program finalists. We find that program participation is associated with an increased likelihood of subsequent entrepreneurship but that this is not uniform across participants; the estimated relationship between program participation and subsequent entrepreneurial activity is disproportionately lower for applicants with ex-ante resources and capabilities in entrepreneurship, measured by prior entrepreneurship experience. Moreover, we only observe this reduced impact of the program on subsequent entrepreneurial activity for participants that have prior experience in founding a technology company as opposed to other forms of entrepreneurial activity. This suggests the program is more effective for individuals that have otherwise limited access to technology entrepreneurship opportunities. Managerial summary: Given the increasingly competitive landscape for entrepreneurship education programs, it is important to understand when and for whom they have the greatest impact. Using 5 years of data from a technology entrepreneurship training program, we show that individuals with a higher predisposition toward the type of entrepreneurship being taught by the program, measured by prior technology entrepreneurship experience, are less likely to benefit from training. Our findings imply that individuals who enter programs with the skill set being taught benefit less from the program at the margin, and that individuals without prior experience can be trained in entrepreneurship. These patterns have implications for entrepreneurial program strategy, individuals considering entry into entrepreneurial careers, and firms deciding whether to develop entrepreneurial capabilities in-house or acquiring them externally.]